Keterkaitan Nilai-nilai Kearifan Lokal Nagekeo dengan Unsur-unsur Budaya Universal - Klemens Mere (Community Engagement and Emergence Journal (CEEJ), 2025)
Local wisdom embodies a community’s worldview and ethical system, yet it often resonates with broader universal cultural elements such as social cohesion, moral order, ecological balance, and intergenerational continuity. This literature review examines how the values of Nagekeo local wisdom in Flores relate to universal cultural elements commonly found across societies. Synthesizing studies published from 2020 onward, the review identifies that Nagekeo values—expressed through communal rituals, oral traditions, local moral narratives, and shared work ethics—align with universal patterns of cultural sustainability and collective identity. The findings show that Nagekeo’s emphasis on communal solidarity, respect for elders, reciprocal support, and human–nature harmony parallels universal cultural principles that support social resilience and ethical life. However, globalization and modernization can weaken the transmission of these values if local culture is treated as symbolic rather than lived practice. The review argues that recognizing Nagekeo wisdom as part of universal cultural structures provides a stronger rationale for integrating it into education, community revitalization programs, and cultural heritage initiatives.